Estimates of Phenotypic Parameters for Milk Production Traits in Romanian Black Spotted Breed Dairy Cows - Eleonora Nistor; Vasileios Bampidis; Marcel Matiuti; Marius Pentea; Lenuta Pet; Valeria Ciolac (Scientific Papers Animal Science and Biotechnologies, 2023)
The present study was designed to evaluate the phenotypic parameters (milk, fat, protein) in a herd of 120 Romanian black spotted dairy cows, in the third lactation, from Dambovita farm, Timis County. Milk samples were collected each day for 305-day lactation. Lactation records for milk, fat, and protein production of dairy cows were analyzed by fitting a multiple trait animal model using restricted maximum likelihood. Results indicated that average milk yield in the studied herd was 5493.78 ± 991.11 kg; fat yield 212.53 ± 37.85 kg and protein yield 173.26 ± 31.13 kg. The mean percentage of fat in the milk was 3.9 while that of protein was 3.2. Values of phenotypic correlation estimated between total 305-day milk, fat, and protein yields ranged from 0.88 to 0.92. Between milk production, milk fat percentage and protein percentage, it was a negative correlation of – 0.26 and – 0.24 respectively. For all parameters examined, phenotypic variability was moderate (less than 20%) which indicates a relatively homogeneous nucleus. The existence of strong positive correlation between milk production and fat yield, but especially between milk production and protein yiled, help the farmers to make the selection of plus variations and to increase the production.